Enterprise Data Warehouses: A conceptual framework for a successful implementation - Simões, Dora
Currently, Data Warehouse systems are a powerful technological tool for managing business information in order to support the processes of decision making at the strategic level more effectively. To better understand the extent to which these systems are or not contributing to the success of business initiatives, the author has developed an extensive study on the implementation of these systems in wider business organizations. Thus, the first purpose of the present paper is to report the results of a review of the state-of-the-art on the architectures of the most used Enterprise Data Warehouse systems, and the level of success achieved against the objectives established beforehand. This work also addresses the methodologies followed in the implementation of the various architectures. The comparison between the different architectures used in most business environments is also made under the two most relevant dimensions for the business stakeholders: time and cost. It is a major objective of the author to contribute in this paper with a conceptual framework aimed at guiding the business actors in the selection of the architecture that best fits their organization, considering the hierarchical level of organization that is supposed to support the Data Warehouse, in which the domain is applied and some considerations about the profile of users in each infrastructure. It is also an objective of this study, to indicate a set of metrics to evaluate the performance of an Enterprise Data Warehouse as well as to establish guidelines on how to proceed to make that assessment.